2022
DOI: 10.1155/2022/9538512
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Gut-Heart Axis and Network Pharmacology to Reveal the Mechanisms of the Huoxue Wentong Formula Against Myocardial Ischemia

Abstract: Background. Myocardial ischemia (MI) is a major public health problem with high mortality and morbidity worldwide. Huoxue Wentong formula (HX), a traditional Chinese medicine (TCM) formula, exhibits unambiguous effects on treating MI and preventing cardiovascular diseases. However, the molecular mechanism of the therapeutic effects of HX on MI remains largely unknown. Objective. This study combined microbiology, metabolomics, and network pharmacology to explore the relationship between the gut microbiota and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 75 publications
(66 reference statements)
0
1
0
Order By: Relevance
“…Traditional Chinese medicine (TCM) has a long history of treating MI. Our research group has previously found that blood-activating Chinese herbal medicine has an improving efect on ischemic heart disease [5][6][7]. Xuefu Zhuyu Capsule (XFC) is a TCM formula that originated from the Qing Dynasty, which has the function of promoting blood circulation, removing blood stasis, moving Qi, and relieving pain, and is widely used in various CVD [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Traditional Chinese medicine (TCM) has a long history of treating MI. Our research group has previously found that blood-activating Chinese herbal medicine has an improving efect on ischemic heart disease [5][6][7]. Xuefu Zhuyu Capsule (XFC) is a TCM formula that originated from the Qing Dynasty, which has the function of promoting blood circulation, removing blood stasis, moving Qi, and relieving pain, and is widely used in various CVD [8][9][10].…”
Section: Introductionmentioning
confidence: 99%